Effect of vitamin D on oxidative stress and serum inflammatory factors in the patients with type 2 diabetes - Jie‐Chao Gu; Yue‐Guan Wu; Weigang Huang; Xiu‐Jing Fan; Xin‐Hao Chen; Biao Zhou; Zhi‐Jun Lin; X. Feng (2022)
Abstract The type 2 diabetes mellitus (T2DM) is an urgent global health problem. T2DM patients are in a state of high oxidative stress and inflammation. Vitamin D and glutathione (GSH) play crucial roles in antioxidation and anti‐inflammation. However, T2DM patients have lower vitamin D and GSH levels than healthy persons. A randomized controlled trial was conducted to see the effect of the vitamin D supplementation on oxidative stress and inflammatory factors in T2DM patients. In this study, a total of 178 T2DM patients were randomly enrolled, 92 patients received regular treatment (T2DM group) and 86 patients in Vitamin D group received extra vitamin D 400 IU per day in addition to regular treatment. Serum vitamin D, GSH, GSH metabolic enzyme GCLC and GR, inflammatory factor MCP‐1, and IL‐8 levels were investigated. We found that the T2DM group has significantly higher concentrations of MCP‐1 and IL‐8 than those in the healthy donor group. After vitamin D supplementation for 90 days, T2DM patients had a 2‐fold increase of GSH levels, from 2.72 ± 0.84 to 5.76 ± 3.19 μmol/ml, the concentration of MCP‐1 decreased from 51.11 ± 20.86 to 25.42 ± 13.06 pg/ml, and IL‐8 also decreased from 38.21 ± 21.76 to 16.05 ± 8.99 pg/ml. In conclusion, our study demonstrated that vitamin D could regulate the production of GSH, thereby reducing the serum levels of MCP‐1 and IL‐8, alleviating oxidative stress and inflammation, providing evidence of the necessity and feasibility of adjuvant vitamin D treatment among patients with T2DM. On the other hand, vitamin D and GSH levels have important diagnostic and prognostic values in T2DM patients.